KOMODIFIKASI TUBUH PEREMPUAN DALAM KUASA SIMBOLIK IKLAN CITRA DAN WRP - KAHFI DIRGA CAHYA; SONIA GABRIELLA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
Women’s bodies are often used as commodities in advertisements. Product labels assume women’s bodies have an exchange value in marketing their products, so that in advertising related to women, there are standards that are constructed. In the space of capitalism, advertisements played by women become commodities that benefit several parties. In advertisements, women become good objects and sell well in the market, especially for products that display women’s bodies. Beauty and body of many women are shown, thus giving various impressions that support the image of advertising. There is a form of commodification in an advertisement related to a woman’s body, so that it can attract women to follow beauty standards according to the ad. This is also related to the efforts of symbolic power towards women’s bodies. The author chose the image of "natural glowing white UV" and WRP "lose weight" ads as analyzed because the message delivered in the ad defines the white and slim body that has been liked by the public. This article was written using the Data source approach obtained by the video advertisement of Citra and WRP.